2001
DOI: 10.1143/jjap.40.6956
|View full text |Cite
|
Sign up to set email alerts
|

C-Axis-Oriented Ru Thin Films Prepared by Sputtering in Ar and O2 Gas Mixture

Abstract: C-axis-oriented Ru thin films were deposited on glass substrates by sputtering a Ru target in Ar and O 2 gas mixture with O 2 flow ratios which were lower than that required for RuO 2 formation. A minimum value of 3.5 • was obtained for the full-width at half maximum (FWHM) of the rocking curve of a Ru (002) peak for the Ru film deposited at a substrate temperature of 500 • C and O 2 flow ratio of 4%. The c-axis-oriented Ru films were observed to be formed from the initial stage of crystal growth and became co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…The success of this experiment confirmed that the deposition of metallic ruthenium is possible even under conditions using a small amount of an oxidant such as oxygen. Furthermore, the XRD pattern showed an enhanced (002) signal intensity, which is consistent with the characteristics of C -axis-oriented Ru thin films that were deposited on glass substrates using dc magnetron sputtering in a mixture of argon and ambient O 2 . This is attributed to the fact that the (001) crystallographic planes have the closest interplanar spacing and that the adsorbed oxygen atom may decrease the surface free energy and enhance the (001) preferential orientation.…”
Section: Resultssupporting
confidence: 77%
“…The success of this experiment confirmed that the deposition of metallic ruthenium is possible even under conditions using a small amount of an oxidant such as oxygen. Furthermore, the XRD pattern showed an enhanced (002) signal intensity, which is consistent with the characteristics of C -axis-oriented Ru thin films that were deposited on glass substrates using dc magnetron sputtering in a mixture of argon and ambient O 2 . This is attributed to the fact that the (001) crystallographic planes have the closest interplanar spacing and that the adsorbed oxygen atom may decrease the surface free energy and enhance the (001) preferential orientation.…”
Section: Resultssupporting
confidence: 77%
“…This unusual characteristic is consistent with the presence of C-axis ori- on glass substrates using dc magnetron sputtering in a mixture of argon and ambient O 2 . [25] The formation of such structure can be attributed to the smaller inter-planar spacing of the (001) crystallographic planes, on which unidirectional thin film growth is more favorable due to the lower surface free energy thus leading to the (001) preferential orientation. For these thin films the XPS analysis detected a reduced amount of carbon (1 %) and oxygen (2 %).…”
Section: Deposition Of Ru Metalmentioning
confidence: 99%
“…In accordance with this hypothesis, a high quality c-axis oriented Ru thin film was deposited on a glass substrate using dc magnetron sputtering. 19 The deposition of Ru metal thin films was next conducted with complex (1) as the CVD precursor and a mixture of 2% oxygen in argon as the alternative carrier gas. The selection of this deposition parameter was encouraged by a recent report that the oxygen could enhance the oxidative ligand decomposition, resulting in metal deposition at lower temperatures, and then affecting the phase and other physical properties of the as-deposited thin film.…”
Section: Deposition Of Ru Metal Thin Filmsmentioning
confidence: 99%